12. CURRENT STATUS AND SOME FACTOR RELATED TO ADVERSE DRUG REACTION REPORT AT NGHE AN GENERAL FRIENDSHIP HOSPITAL IN 2023 (Vietnam Journal of Community Medicine, 2024)
Objective: Describe the current situation and some factors related to reporting adverse drug reactions (ADR) at Nghe An General Friendship Hospital in 2023.Research methods: Cross-sectional descriptive study with evaluation conducted on 130 reports of adverse drug reactions and 27 medical staff at Nghe An General Friendship Hospital from October 2023 to April 2024.Research results: ADR reports with complete information accounted for 96.2%, mainly by nurses (70.3%). The average age of patients is 52.62 ± 21.65, the majority are in the age range of 18-60 (50.8%); The male/female ratio is 0.9. Infectious and parasitic diseases have the highest rate (34.38%), followed by respiratory system diseases (15.63%). There were 46 active ingredients/135 active ingredients with recorded ADRs, of which Vancomycin, Amoxicillin/Clavulanic Acid and Ceftizoxim were the most recorded active ingredients (13.28%, 9.38% and 9.38%). Skin reactions account for the highest rate (44.3%); Some general manifestations and respiratory disorders were 14.9%, 14.5%, respectively. Manifestations on the skin and mucous membranes include: itching (20.6%); rash (13.6%); red skin, flushing (10.3%). Mild and moderate ADR manifestations account for the highest proportion (67.2%).The reason for not reporting an ADR shared by medical staff is that they are overloaded with work and do not have time to report (51.9%). Most medical staff have no difficulty reporting ADRs (48.1%). However, difficulty identifying the suspected drug (33.3%), lack of time (22.2%), and difficulty determining the severity of the ADR (18.5%) are also main obstacles. The main proposed measure is to promote coordination between doctors, pharmacists and nurses to support ADR reporting (63%).Conclusion: ADRs causing skin reactions account for the highest rate (44.3%); Some general manifestations and respiratory disorders were 14.9% and 14.5%, respectively. Vancomycin causes ADR with the highest rate of allergy, erythema, difficulty breathing, and chest pain (10.94%), while Amoxicillin/Clavulanic Acid causes allergy and low blood pressure (8.59%).
Keywords: ADR, adverse drug reactions, Nghe An General Friendship Hospital.